IMPACT OF TV ADVERTISEMENT ON CUSTOMERS PURCHASING DECISION IN NANGARHAR PROVINCE - Fathullah Shinwari; Hayatullah Ashna; Ehsanullah Eshan (International Journal of Contemporary Issues in Social Sciences, 2024)
Advertising is a way of communication to convince an audience for taking purchase decision about a product or service and delivering information to viewers. The main purpose of this study is to examine the relationship between TV advertisements on Customers purchasing decision in Nangarhar, Jalalabad. A non-probability random sampling method was used in this research. Through non-probability random sampling, 172 respondents were interviewed. Population for the study included all students of Nangarhar University. Data for the study were gathered from students of different faculty using an adopted questionnaire. Finally, 172 questionnaires were given to the respondents, and after 2 weeks, data from all respondents were returned. For data analysis used SPSS software, and different tests were checked. Finally, the findings of this study demonstrated that television advertisements had a beneficial impact on students’ purchase decisions in Nanagarhar, and that this effect is statistically significant. Students can use television advertisements to purchase things they require and locate locations where they are available.